2007
DOI: 10.1089/ten.2006.0150
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Human Umbilical Cord Matrix Stem Cells and Temporomandibular Joint Condylar Chondrocytes for Tissue Engineering Temporomandibular Joint Condylar Cartilage

Abstract: The temporomandibular joint (TMJ) presents many problems in modern musculoskeletal medicine. Patients who suffer from TMJ disorders often experience a major loss in quality of life due to the debilitating effects that TMJ disorders can have on everyday activities. Cartilage tissue engineering can lead to replacement tissues that could be used to treat TMJ disorders. In this study, a spinner flask was used for a period of 6 days to seed polyglycolic acid (PGA) scaffolds with either TMJ condylar chondrocytes or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 49 publications
2
122
0
1
Order By: Relevance
“…In the first application of these cells for fibrocartilage engineering, hUCMSCs outperformed native mandibular condylar cartilage cells, leading to higher cellularity and superior matrix production. 12 We further optimized the cell seeding density in PGA scaffolds and reported that a density larger than 25 million per ml was recommended to maintain the scaffold integrity and retain enough cells and extracellular matrix for fibrocartilage engineering. 13 In the current study, we specifically focused on the usage of bioactive signals (TGF-b3 and IGF-I) to better promote cell proliferation and enhance cartilage-specific matrix synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first application of these cells for fibrocartilage engineering, hUCMSCs outperformed native mandibular condylar cartilage cells, leading to higher cellularity and superior matrix production. 12 We further optimized the cell seeding density in PGA scaffolds and reported that a density larger than 25 million per ml was recommended to maintain the scaffold integrity and retain enough cells and extracellular matrix for fibrocartilage engineering. 13 In the current study, we specifically focused on the usage of bioactive signals (TGF-b3 and IGF-I) to better promote cell proliferation and enhance cartilage-specific matrix synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]9,10 In chondrogenic differentiation, transforming growth factor-beta isoforms (TGF-b1, b2, and b3) are known to play an important role. 11 In cell pellets [4][5][6] and polyglycolic acid (PGA) scaffolds, 12,13 TGF-b1 4,12,13 or -b3 5,6 have been incorporated into serum-free media to induce chondrogenic differentiation of hUCMSCs in 2-3 weeks, which was revealed by a positive immunostaining for type II collagen [4][5][6]12,13 and aggrecan. 12,13 Insulin-like growth factor-I (IGF-I), an important anabolic agent for several different tissues in the body, [14][15][16] has been demonstrated by most studies to have little or no effect on chondrogenic differentiation in the presence of insulin-transferrin-selenium (ITS) with MSCs, 17,18 but promoted proliferation and biosynthesis in vitro of both mature hyaline cartilage and fibrocartilage cells.…”
mentioning
confidence: 99%
“…Termed 'human umbilical cord matrix cells' (HUCM), the immature progenitor cells have been found to possess multipotent differentiation capacity, as indicated by successful transformation into adipocytes, chondrocytes, osteoblasts and myoblasts (Can and Karahuseyinoglu, 2007). A few studies focused on chondrogenic differentiation of HUCM in 3D culture, during which GAGs as well as collagen I and II were detected histologically (Bailey et al, 2007;Karahuseyinoglu et al, 2007;Wang et al, 2004Wang et al, , 2008. In contrast to BMSC and ASC, which have been demonstrated to possess the ability to synthesize hyaline-like cartilage, the expression of collagen type II and aggrecan is decreased in HUCM, indicating the synthesis of fibrous tissue (Hildner et al, 2010b;.…”
Section: Referencementioning
confidence: 99%
“…Stem cells from human exfoliated deciduous teeth and periodontal ligament stem cells can also be used in order to create nearly identical forms of their naturally formed structures [9]. Tissue engineering of the temporomandibular joint from stem cells is also possible [1,7,[10][11][12][13] as a result and takes place in a similar manner to that of the aforementioned tissues and muscles, with more of an emphasis on cell density in order for the tissues to be properly formed. Another important aspect of craniofacial muscle tissue engineering is gene delivery, which is possible through periodontal tissue engineering, having a primary focus on gene transfer and its main benefits such as stimulation of the tissue engineering of periodontal defects.…”
Section: Introductionmentioning
confidence: 99%